2012
DOI: 10.1136/bmj.e3874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telehealth on use of secondary care and mortality: findings from the Whole System Demonstrator cluster randomised trial

Abstract: Objective To assess the effect of home based telehealth interventions on the use of secondary healthcare and mortality.Design Pragmatic, multisite, cluster randomised trial comparing telehealth with usual care, using data from routine administrative datasets. General practice was the unit of randomisation. We allocated practices using a minimisation algorithm, and did analyses by intention to treat. Setting 179 general practices in three areas in England.Participants 3230 people with diabetes, chronic obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
455
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(472 citation statements)
references
References 37 publications
8
455
1
8
Order By: Relevance
“…While new technologies open up the possibilities for new healthcare products and services there has been limited uptake within the medical profession, particularly within the UK [ 29 ]. This means that the potential benefits of telehealth, such as its ability to reduce hospital admissions [ 62 ] and improve quality of life for patients [ 69 ] are not being realized at a large enough scale to generate the benefits that promise to bridge the gap between available health resources and user demand.…”
Section: Key Sum M Ary Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…While new technologies open up the possibilities for new healthcare products and services there has been limited uptake within the medical profession, particularly within the UK [ 29 ]. This means that the potential benefits of telehealth, such as its ability to reduce hospital admissions [ 62 ] and improve quality of life for patients [ 69 ] are not being realized at a large enough scale to generate the benefits that promise to bridge the gap between available health resources and user demand.…”
Section: Key Sum M Ary Pointsmentioning
confidence: 99%
“…In order to maintain services into the future, healthcare providers and commissioners are beginning to consider new ways of delivering healthcare services that harness technological advancements to improve efficiency and quality by treating people in their own homes; for example, the use of teleconferencing for patient consultations, smart phone apps to deliver healthcare information, and in-home equipment for the monitoring of patient vital signs. There are many examples of how the use of telehealth equipment can not only improve the health of the patient and the quality of the care they receive, but also improve the efficiency and the capacity of existing services [ 62 ]. For example, for the UK prison service, some local hospitals have developed the capability to offer hospital outpatient appointments to prisoners remotely through the use of video conferencing, meaning prisoners can access care without the costly need to leave the prison environment NHS [ 53 ].…”
Section: Key Sum M Ary Pointsmentioning
confidence: 99%
“…One of the reasons for this recalcitrance may be the lack of studies that have progressed beyond pilot scale; there is also criticism of the quality of the available evidence [4]. The better known large studies are the UK's Whole System Demonstrator projects [5] and the USA Veterans' Administration's implementation [6]. These found significant reductions in hospital admissions and re-admissions, and other benefits.…”
Section: Introductionmentioning
confidence: 99%
“…10 Other studies have shown that telemonitoring is associated with lower rates of mortality for patients. 5,8,14 For people with diabetes, Telehealth programs have resulted in patients making fewer clinic visits 7 and having considerably fewer hyperglycaemic and hypoglycaemic events.…”
mentioning
confidence: 99%
“…5 Telehealth has been shown to improve health outcomes [8][9][10][11] and reduce health service use in specialities such as chronic heart failure, respiratory conditions and diabetes management. 8,9,12,13 In chronic heart failure, there is evidence that telemonitoring not only reduces hospital admissions, but may also be effective for disease management in high-risk patients.…”
mentioning
confidence: 99%